2000
DOI: 10.1111/j.1346-8138.2000.tb02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis Rubra Pilaris (PRP): Report of Four Cases

Abstract: Four patients with pityriasis rubra pilaris are reported. The diagnosis in each was based upon well-recognized clinical features. Two of them, a mother and son, had the disease since childhood and were marked by relative remission in spring and exacerbation in autumn. Moderate to severe pruritus was a common dominator. Erythroderma was a presenting feature in one case. Although histopathology was considered imperative, it only supplemented the clinical expression. Vitamin A in heavy dosage, supplemented by vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[1][2][3] Those rare familial cases demonstrate autosomal-dominant inheritance with an early age of onset, incomplete penetrance, and variable expression. [3][4][5][6][7][8] Griffiths classified PRP into five types on the basis of age of onset, clinical features, and prognosis; these types are classic adult type I, atypical adult type II, classic juvenile type III, circumscribed juvenile type IV, and atypical juvenile type V. 9,10 More recently, a type VI PRP, or human immunodeficiency virus (HIV)-associated PRP, has been described. [11][12][13][14] Familial PRP belongs to the type V group, which accounts for about 5% of all cases.…”
Section: Pityriasis Rubra Pilaris (Prp [Mim 173200]mentioning
confidence: 99%
“…[1][2][3] Those rare familial cases demonstrate autosomal-dominant inheritance with an early age of onset, incomplete penetrance, and variable expression. [3][4][5][6][7][8] Griffiths classified PRP into five types on the basis of age of onset, clinical features, and prognosis; these types are classic adult type I, atypical adult type II, classic juvenile type III, circumscribed juvenile type IV, and atypical juvenile type V. 9,10 More recently, a type VI PRP, or human immunodeficiency virus (HIV)-associated PRP, has been described. [11][12][13][14] Familial PRP belongs to the type V group, which accounts for about 5% of all cases.…”
Section: Pityriasis Rubra Pilaris (Prp [Mim 173200]mentioning
confidence: 99%
“…Nevertheless, several reports have clearly demonstrated that the entity has three distinct age groups of peak occurrence, namely early childhood (0-10 years), late childhood (11-19 years), and adulthood (40-60 years). [3][4][5][15][16][17][18][19][20][21][22] Furthermore, in childhood, males are affected more often than females (male to female ratio, 3 : 2), 7 unlike adult PRP in which males and females are affected equally. Differences in PRP can be seen in different races.…”
Section: Epidemiologymentioning
confidence: 99%
“…However, its occurrence among members of a single family is yet another intriguing divulgence emphasizing a possible autosomal dominant expression. Such cases were largely limited to atypical juvenile PRP type V 10 ; a similar situation may occasionally be encountered in an adult classic type I 11 . Familial PRP cases are too few and far between.…”
Section: Discussionmentioning
confidence: 98%
“…Apparently normal skin “islets of sparing” punctuate these lesions (adult classic type I) 1,2,4 . The details of the pattern and natural history of the disease were delineated earlier, keeping in view age‐at‐onset, behavior, clinical appearance, and prognosis 1–3,9 : adult classic, type I; atypical, type II; classic, type III; circumscribed, type IV; and atypical, type V. Nail changes are reported in the form of distal yellow‐brown discoloration nail plate thickening (onychauxis), splinter hemorrhages, and subungual hyperkerotosis 10–14 . In addition, pitting, similar to psoriasis and longitudinal ridging of the nails, may be a feature 5 .…”
Section: Discussionmentioning
confidence: 99%